PERBEDAAN HASIL KEMAMPUAN BERPIKIR KRITIS DAN BERPIKIR KREATIF SISWA MENGGUNAKAN HANDOUT BERBASIS PEMECAHAN MASALAH - Hasanah, Uswatun; Gummah, Syifa’ul; Herayanti, Lovy (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2018)
This study aims to determine the effect of problem solving handouts on students critical thinking skills and the effect of problem-solving handouts on the students creative thinking ability and the difference in learning outcomes of the two measured thinking skills after learning using handout-based physics problem solving on static fluid materials. The study population is all students of class XI MIA SMAN 1 Praya Timur with research sample consist of two classes that class XI MIA 1 as critical thinking experiment group and class XI MIA 2 as experiment group of creative thinking. Both samples are taught using handout-based troubleshooting. The instrument used in this study uses critical thinking test and essay of creative thinking. The result of analysis of class XI MIA 1 data obtained pretest average value of 45.1 and posttest of 75.3 so obtained Sig value. (2-tailed) data (0.00) < alfa test (0.05). This result indicates that there is influence of problem solving handout to critical thinking skill of XI MIA class 1. The result of analysis of class XI MIA 2 data obtained pretest value of equal to 35,9 and posttest of 62,4 so obtained by Sig value. (2-tailed) data (0.00) < alfa test (0.05). These results indicate that there is a problem-based handout effect on problem-solving thinking ability of XI MIA class 2 students. The average difference in learning outcomes from both experimental groups of critical thinking and creative thinking suggests that learning using handouts based on problem solving is more appropriate to be used to train students ’critical thinking skills are compared to train students’ creative thinking skills.